2016
DOI: 10.4093/dmj.2016.40.6.482
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course and Risk Factors of Diabetic Retinopathy in Patients with Type 2 Diabetes Mellitus in Korea

Abstract: BackgroundWe investigated clinical course and risk factors for diabetic retinopathy (DR) in patients with type 2 diabetes mellitus (T2DM).MethodsA total of 759 patients with T2DM without DR were included from January 2001 to December 2004. Retinopathy evaluation was performed at least annually by ophthalmologists. The severity of the DR was classified into five categories according to the International Clinical Diabetic Retinopathy Severity Scales.ResultsOf the 759 patients, 523 patients (68.9%) completed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 44 publications
4
32
3
2
Order By: Relevance
“…32 One study in China also found that the higher systolic blood pressure, higher HbA1c, higher fasting plasma glucose, higher LDL-c and lower TG were important factors to increase the risk of DR. 33 However, another study in China also showed that higher systolic blood pressure, higher HbA1c, and lower body mass index were associated with the presence of DR. 34 A study from South Korean also confirmed that higher HbA1c was the significant risk factor for the incidence of DR risk in patients with T2DM. 28 Comparing to those results, the increased risk of DR was caused by higher HbA1c and higher LDL-c which were consistent with our study, but TG and CHOL-T were not. Thus, well control and manage for HbA1c and LDL-c should significantly decrease the chance of developing DR in diabetes or prevent from the progression of diabetic retinopathy in diabetes patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…32 One study in China also found that the higher systolic blood pressure, higher HbA1c, higher fasting plasma glucose, higher LDL-c and lower TG were important factors to increase the risk of DR. 33 However, another study in China also showed that higher systolic blood pressure, higher HbA1c, and lower body mass index were associated with the presence of DR. 34 A study from South Korean also confirmed that higher HbA1c was the significant risk factor for the incidence of DR risk in patients with T2DM. 28 Comparing to those results, the increased risk of DR was caused by higher HbA1c and higher LDL-c which were consistent with our study, but TG and CHOL-T were not. Thus, well control and manage for HbA1c and LDL-c should significantly decrease the chance of developing DR in diabetes or prevent from the progression of diabetic retinopathy in diabetes patients.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the prevalence of DR in patients would rise substantially when the patient's diabetic durations were over 10 years. 27 Some studies also found that the longer duration of diabetes, the higher chance of retinopathy appeared; with impact on the risk of DR. 17,24,28 The result of those studies were corresponding to our study. Therefore, well controlled earlier could prevent and delay the progression of DR in patients with diabetes.…”
Section: Discussionsupporting
confidence: 83%
“…). A total of 17 studies met the inclusion criteria (Table ). Fourteen studies were based on predominantly white populations in one of 10 different Western countries.…”
Section: Resultsmentioning
confidence: 99%
“…The STDR incidence rates of people without retinopathy at last screening session varied from 0.27 to 1.5 per 100 person‐years (Table ). The studies reported different types of STDR, therefore, results are only partially comparable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation